Market Value of Equity Model before and after the Implementation of IFRS - Bakti Setyadi; Fitriasuri Fitriasuri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examined the impact of IFRS convergence on the structural model of Market Value of Equity. Determinants tested that affect to Market Value of Equity (MVE) are Earnings per Share (EPS), Equity per Share (EQPS), Price per Share (PPS). The researchers observed the difference of Market Value of Equity models through a comparison of regression analysis results and structural models before and after IFRS convergence. The method used is a survey method using secondary data spesifically of financial statements with quantitative analysis techniques in the sector of trade in goods and services listed on the Indonesian stock exchange. The results show that the EPS has a significant influence on the MVE after the adoption of IFRS, whereas before the application of IFRS, EPS has no influence on MVE. In the contrary to these results, EQPS has an influence on MVE prior to the application of IFRS, whereas after the adoption of IFRS, EQPS has no influence on MVE. Furthermore, PPS has an influence on MVE both before and after the implementation of IFRS. However, EPS, EQPS and PPS simultaneously have positive impact to MVE, both before and after the implementation of IFRS. In terms of Goodness of Fit, the structural equation model before IFRS convergence is better than it is after IFRS convergence (based on AICtest, SIC test and Hannan-Quinn criter).